Respiratory and non-respiratory symptoms associated with pesticide management practices among farmers in Ghana's most important vegetable hub. - Quansah, R.; Bend, J.R.; Armah, F.A.; Bonney, F.; Aseidu, J.; Yawson, D.O.; Adu, M.O.; Luginaah, I.; Essumang, D.K.; Abdul-Rahaman, A.; Cobbina, S.; Iddi, S.; et al. (Environmental Monitoring and Assessment, 2019)
The data presented here are from the Offinso North District Farm Health Study (ONFAHS), a population-based cross-sectional study among vegetable farmers in Ghana. The paper addresses knowledge, pesticide handling practices, and protective measures related to pesticide use by self-reported symptoms for 310 adult farmers who completed a comprehensive questionnaire on pesticide management practices and health. In addition, an inventory was prepared using information supplied by pesticide sellers/dealers in this district. We report that cough and wheezing (but not breathlessness) are positively associated with stirring pesticide preparations with bare hands/drinking water while mixing/applying pesticides, and stirring pesticide preparations with bare hands/drinking water/smoking cigarettes while mixing/applying pesticides. There is a significant exposure-response association between the number of precautionary measures practiced while handling pesticides and cough and wheezing but not with breathlessness. We also found unsafe practices to be associated with sexual dysfunction, nervousness, and lack of concentration. The results also suggest a negative association between practice of any precautionary measure when mixing/applying pesticides and sexual dysfunction, nervousness, and lack of concentration. We found that in spite of the fact that farmers have adequate knowledge about the environment and health effects of pesticides, several unhygienic practices are in widespread use, indicating that knowledge is not necessarily always translated in action. Further action is necessary to promote the safe use of pesticides and to replace existing poor management practices among these and other farmers in Ghana.
Research Article
Keywords: Farms; Ghana; Pesticide handling; Safety; Vegetable farmers; Symptoms